The Space-Variant Phase-Error Matching Map-Drift Algorithm for Highly Squinted SAR - Tang, Yu; Zhang, Bo; Xing, Mengdao; Bao, Zheng; Guo, Liang (IEEE geoscience and remote sensing letters, 2013)
In highly squinted synthetic aperture radar (SAR) motion compensation, the map-drift (MD) algorithm cannot estimate the Doppler chirp rate accurately when the range walk is compensated in the azimuthal time domain. This problem stems from the influence of the azimuthal position-dependent (i.e., space-variant) phases, which are introduced by the compensation of the range walk in the azimuthal time domain on the Doppler chirp rate estimation. This letter proposes a space-variant phase-error matching MD algorithm that can improve the precision of estimating the Doppler chirp rate for the highly squinted SAR by removing the influence of the azimuthal position-dependent phases.